Predictors of Tooth Loss in Two US Adult Populations - Lynn B. Copeland, DMD; Elizabeth A. Krall, PhD, MPH; L. Jackson Brown, DDS, PhD, Raul 1. Garcia, DMD (Blackwell Synergy, 2004)
This study determines tooth loss rate over a 1 O-year period and identifies predictors of tooth loss in two separate US adult longitudinal study populations.